Research on the Integration of Discourse System of Chinese Indigenous Art Theory and Art Aesthetics - Wang, Zhiyang; Liu, Feng; Liu, Guangyuan (Applied mathematics and nonlinear sciences, 2024)
The long-term development of Chinese art theory can not be separated from the art theory doctrine system constructed by the West. In order to integrate Chinese art theory with aesthetics, it is necessary to localize the construction of Chinese art theory. This paper starts from the foundation of Chinese art aesthetics and proposes the direction of the construction of the Chinese art aesthetic discourse system. Based on the guidance of art discourse graph theory, combined with the BERT extractive summary model, the discourse relationship system is divided into four steps: task determination, vector representation of discourse units, graph encoder establishment, and discourse unit selection. Applying the model to reality analysis, the results are as follows: “art definition” is the keyword with the highest frequency and centrality in the field of art theory and aesthetic fusion after appearing in 2017, which is 295 times and 0.896, respectively. Art theory and aesthetic fusion of art are separated into two stages, based on 2020 as the demarcation line. After 2020, the keyword intensity becomes “empathy”, “modern art,” and “art aesthetics”, with an intensity of 4.4966, 3.4321, and 3.4565, respectively. China’s local art theories are shifting towards art aesthetics, and the integration is a natural process.